Thoracic imaging - Desai, Sujal, 1962- ([Oxford] : Oxford University Press, 2012)
Packed with over 600 illustrations, this practical handbook covers both the key principles of thoracic imaging, including the relevant principles, dose considerations, and radiological signs and their meaning, and the different pulmonary diseases.
Also issued in print format.
Description based on online resource; title from home page (viewed on Oct. 30, 2012).
Includes bibliographical references and index.
Keywords: Lungs -- Imaging